FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SERTA DAMPAKNYA TERHADAP PRESTASI KERJA APARATUR SIPIL NEGARA DI KABUPATEN BANGKA TENGAH - Muhammad Sahri; Amri Amri (LPPM STIE PERTIBA Pangkalpinang, 2019)
The purpose of this study was to analyze the influence of leadership, organizational culture, organizational communication, motivation, and training on the performance that impacts work performance. Respondents are employees of the secretariat of the district of Central Bangka with a total of 40 people. The method of analysis uses path analysis. The results of the study concluded that there is an influence of leadership variables, organizational culture, organizational communication, motivation, training on the Regional Secretariat of Central Bangka Regency. The recommendations of this study are expected to further enhance the knowledge of leaders in all fields and institutions to provide support and appreciation to improve performance on employee work performance